Carbon and nitrogen flux through the Cape rock lobster jasus lalandii (H. Milne Edwards), with particular reference to the nearshore Benguela system - Zoutendyk, Peter (Department of Biological Sciences, 2014)
Bibliography: leaves 169-198.